Impact of the covid-19 pandemic on care and on the use of telemedicine in otorhinolaryngology: The portuguese reality - C. Gonçalves, Ana Isabel (2021)
Introduction: The 2019 coronavirus disease (COVID-19) pandemic has led to profound restructuring in healthcare systems worldwide. Health institutions focused their resources on the approach to COVID-19 and activities were restricted in other areas. On the other hand, the use of telemedicine was stimulated, which consists of providing clinical and educational services remotely, but maintaining the interaction in real time, using audiovisual media. The specialty of Otorhinolaryngology (ENT) represents one of the many specialties whose clinical and surgical activities have undergone changes, due to the measures imposed.  Objectives: We intend to assess the impact of COVID-19 on the provision of care and the use of telemedicine in ENT in Portugal, during the State of Emergency (march 22 to may 2, 2020), in the hope that these data may be useful as a future reference in future waves of COVID-19 or in a possible new public health threat, always aiming to improve the health care provision.  Material and Methods: Application of an anonymous questionnaire, developed through the Google Forms tool and sent by e-mail to all Directors/Coordinators / of ENT Departments/Units in the country. The questionnaire comprises 35 questions with multiple or simple answers.  Results: We obtained a 56.5% response rate to the questionnaire. Prior to the beginning of the pandemic, only 7.7% of the Departments used telemedicine, in the form of telephone contact and electronic medical prescription (EMP). In turn, during the State of Emergency, 84.6% started using telemedicine. During this period, 96.2% of the Departments maintained restricted clinical activity and 3.8% did not maintain any activity at all, with the majority maintaining less than 50% of their usual activity. Regarding the consultation and operating room activity, 96.2% of the Departments only performed urgent/oncological consultations and 80.8% only performed urgent surgeries/scheduled oncological pathology, with 3.8% not having any consultation and 19,2% had no surgical activity at all. Of all ENT Departments that participated in this study, 57.7% do not consider that there was an increase in contacts by patients during the State of Emergency. Once the COVID-19 pandemic has been overcome, 65.4% of the Departments considered they can implement/maintain the use of telemedicine in specific situations, namely, in most cases (82.4%) by telephone contact with the patient and EMP. In normal conditions, 46.2% consider that telemedicine in ENT adds quality to the service provided to patients, with 50% also considering that this modality improves access to healthcare and that it can be applied, in some situations, to specificities of ENT patients (57.7%). However, 73.1% consider that telemedicine is not applicable to most patients, due to literacy issues.  Conclusions: The State of Emergency that prevailed in our country, due to the COVID-19 pandemic, changed the clinical practice in ENT, with the suspension of the presential elective activity in all ENT Departments, with a bet on telemedicine, as a way to allow the contact with these patients, maintaining only consultation and surgical treatment of urgent and oncological pathologies. This critical period may have stimulated a possible greater future use of telemedicine. However, the clinical impact of these changes on the quality of the service provided and on the health of patients has not been evaluated, so further studies are needed to investigate clinical results and possible health gains.